2018
DOI: 10.1080/2162402x.2018.1512942
|View full text |Cite
|
Sign up to set email alerts
|

HER2 signaling regulates the tumor immune microenvironment and trastuzumab efficacy

Abstract: Through whole-transcriptome profiling of HER2+ breast carcinomas (BCs), we previously showed that those sensitive to trastuzumab are addicted to this oncoprotein and are enriched in immune pathways, raising the hypothesis that HER2 itself regulates immune cell recruitment. In the present study we investigated the relationship between HER2 activity and the pro-trastuzumab tumor immune milieu. Gene expression profiling and immunohistochemistry analysis of 53 HER2+ BCs showed that trastuzumab-sensitive tumors exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 45 publications
1
46
0
Order By: Relevance
“…In line with our results, a recent study has demonstrated that HER2-positive breast cancer patients exhibited a specific tumor transcriptome that conditioned their response to adjuvant trastuzumab (204). The study shows that HER2-positive tumors that were sensitive to trastuzumab treatment had a higher expression of certain chemokines related to an antitumor immune response, to migration of T and B lymphocytes to the tumor bed and monocyte recruitment.…”
Section: Tnfα and The Immune Response Against Cancersupporting
confidence: 91%
See 1 more Smart Citation
“…In line with our results, a recent study has demonstrated that HER2-positive breast cancer patients exhibited a specific tumor transcriptome that conditioned their response to adjuvant trastuzumab (204). The study shows that HER2-positive tumors that were sensitive to trastuzumab treatment had a higher expression of certain chemokines related to an antitumor immune response, to migration of T and B lymphocytes to the tumor bed and monocyte recruitment.…”
Section: Tnfα and The Immune Response Against Cancersupporting
confidence: 91%
“…In particular, it is proposed that CCL2 recruits mainly monocytes to the TME and that its chemokine action is regulated by the PI3K/NF-κB pathway, activated by the HER2 receptor in the plasma membrane. Triulzi et al claim that there is a strong relationship between the expression of immune chemokines like CCL2 together with the infiltration of immune cells in the TME and with the efficacy of trastuzumab treatment in HER2-positive patients (204).…”
Section: Tnfα and The Immune Response Against Cancermentioning
confidence: 99%
“…This review has shown that it has to be taken into consideration that CCL2 has a significant impact on immune cells that goes beyond attraction. Correspondingly, it has recently been shown that the efficiency of trastuzumab relies on CCL2 levels and monocytes present in the TME in mammary carcinoma in vivo (261). A higher CCL2 level also increased the response to chemotherapy (paclitaxel and cisplatin) (262).…”
Section: Discussionmentioning
confidence: 99%
“…The infiltration level of TILs could almost be a predictive factor for therapy response (32). Mechanistically, activated HER2 induces the production of CCL2 (C-C Motif Chemokine Ligand 2) through the PI3K-NF-κB axis, promoting recruitment and activation of infiltrated immune cells (35), and TNBC patients were found to have a higher tumor mutation burden (TMB) and to present neoantigens that are correlated with a more effective immunotherapy response (36), while estrogen and estrogen receptor (ER) signaling appears to have little impact on the immune environment (37). With regard to stromal signatures, cancer-associated fibroblasts (CAFs) are one of the most important stromal cell types in the breast cancer microenvironment.…”
Section: Discussionmentioning
confidence: 99%